Advanced Confocal Microscopy Techniques to Study Protein-protein Interactions and Kinetics at DNA Lesions - Legartová, Soňa; Suchánková, Jana; Krejčí, Jana; Kovaříková, Alena; Bártová, Eva (Journal of visualized experiments, 2017)
Local microirradiation with lasers represents a useful tool for studies of DNA-repair-related processes in live cells. Here, we describe a methodological approach to analyzing protein kinetics at DNA lesions over time or protein-protein interactions on locally microirradiated chromatin. We also show how to recognize individual phases of the cell cycle using the Fucci cellular system to study cell-cycle-dependent protein kinetics at DNA lesions. A methodological description of the use of two UV lasers (355 nm and 405 nm) to induce different types of DNA damage is also presented. Only the cells microirradiated by the 405-nm diode laser proceeded through mitosis normally and were devoid of cyclobutane pyrimidine dimers (CPDs). We also show how microirradiated cells can be fixed at a given time point to perform immunodetection of the endogenous proteins of interest. For the DNA repair studies, we additionally describe the use of biophysical methods including FRAP (Fluorescence Recovery After Photobleaching) and FLIM (Fluorescence Lifetime Imaging Microscopy) in cells with spontaneously occurring DNA damage foci. We also show an application of FLIM-FRET (Fluorescence Resonance Energy Transfer) in experimental studies of protein-protein interactions.
Keywords: geny p53; poškození DNA; DNA Damage; Kinetics; konfokální mikroskopie; Protein Interaction Domains and Motifs; interakční proteinové domény a motivy; Genes, p53; Microscopy, Confocal; kinetika